Reconfigurable ultraviolet and high-energy visible dielectric metamaterials - Gholipour, Behrad (2020)
Photonic materials with tunable and switchable ultraviolet (UV) to high-energy visible (HEV) optical properties may benefit applications such as sensing, high-density optical memory, beam-steering, adaptive optics, and light modulation. Here, for the first time we demonstrate a nonvolatile switchable dielectric metamaterial operating in the UV-HEV spectral range. Nanograting metamaterials in a layered composite of low-loss ZnS/SiO2 and the chalcogenide phase-change medium germanium-antimony-telluride (Ge2Sb2Te5 or GST) exhibit reflection resonances at UV-HEV wavelengths that are substantially modified by light-induced (amorphous-crystalline) phase transitions in the chalcogenide layer. Despite the presence of the lossy GST, resonance quality factors up to Q ∼ 15 are ensured by the transparency (low losses) of ZnS/SiO2 in the UV-HEV spectral range and values of Q increase as the refractive index of Ge2Sb2Te5 decreases, upon crystallization. Notably, however, this switching leaves resonance spectral positions unchanged.